Study of acute pharmacologic effects of prolactin on calcium and water transport in the rat colon by an in vivo perfusion technique - N. Krishnamra (2018)
We investigated the acute effect of intraperitoneally administered prolactin on calcium and water transport in colon of sexually mature female Wistar rats using an in vivo perfusion technique. Test solution containing (in mM) NaCl, 100; KCl, 4.7; MgSO4, 1.2; CaCl2, 20; D-glucose, 11; sodium ferrocyanide (Na4Fe(CN)6), an index of net water transport, 20; and 0.7 (μCi45CaCl2(1 Ci = 37 GBq) was perfused througth the 8-cm colonic loop for 60 min at perfusion rates of 0.5 or 1.0 mL·min-1. Calcium and water transport was also studied under a no flow condition to stimulate the condition often found in the colon by in vivo ligated colonic loop for 30 min. Control results showed no correlation between calcium transport and water flux. Flow of luminal solution at 0.5 and 1.0 mL·min-1was found to reverse net calcium absorption from 0.04 ± 0.01 nmol·g-1dry weight·h-1to net calcium secretion of 0.04 ± 0.04 and 0.9 ± 0.02 nmol·g-1dry weight·h-1, respectively. Neither 0.4, 0.6, nor 1.0 mg·kg-1prolactin had any effect on calcium fluxes in the colon. On the other hand, at a perfusion rate of 1 mL·min-1, 0.4 mg·kg-1prolactin significantly decreased net water absorption from 3.86 ± 0.90 to 0.88 ± 0.64 mL·g-1dry weight·h-1(P < 0.001), and the higher doses of 0.6 and 1.0 mg·kg-1prolactin reversed net water absorption to net water secretion of 2.20 ± 0.63 and 2.33 ± 0.89 mL·g-1dry weight·h-1, respectively (P < 0.001). The stimulatory effect of prolactin on water transport was completely abolished by reducing the perfusion rate from 1.0 mL·min-1to zero. The stimulatory effect of prolactin on water secretion at perfusion rate of 1.0 mL·min-1was also abolished when luminal [Na+] was reduced from 180 to 80 mM. We concluded that, unlike in the small intestine, calcium fluxes in the colon are not related to water transport and did not respond at all to prolactin. Water transport, on the other hand, was reversed from net absorption to secretion by prolactin. We propose that this prolactin-induced water secretion is probably mediated by recycling of luminal sodium in the vicinity of tight junctions.